New derivatives of 2-R1-N-(5-R)-1,3,4-thiadiazol-2-yl-benzolsulfonamides: synthesis, physicochemical properties and biological activity prediction - Sych, I; Perekhoda, L; Іеremina, Z (Annals of Mechnikov's Institute, 2020)
Introduction: The analysis of modern literature, including overseas one, showed that a lot of the scientific researches is devoted to finding and creating biologically active compounds on base 1,3,4-thiadiazole. Derivatives of 1,3,4-thiadiazole are the large group of heterocyclic compounds with high rates of antimicrobial, antituberculosis, antidiabetic, antineoplastic and anticonvulsant activity. Material and methods: The purpose of this study was the expansion of sulfone derivatives substituted nitrogen-containing heterocyclic systems through the synthesis of 2-R1-N (5-R)-1,3,4-thiadiazol-2-ilbenzolsulfonamides and prediction their pharmacological activity for future planning pharmacological screening. Synthesis of semi-products 2-amino-5-R-1,3,4-thiadiazoles was carried out by cyclization thiosemicarbazide and substituted derivatives of carboxylic acids in the presence of concentrated sulfuric acid. The synthesis oftarget compounds 2-R1-N(5-R)-1,3,4-thiadiazol-2-ylbenzolsulfon-amides was carried out by N-acylation of 2-amino-5R-1,3,4-thiadiazole substituted benzolsul-fochlorides in the presence of anhydrous pyridine. The reaction proceeds by the classic SN2-mechanism.The resulting compounds are white crystalline substances, soluble in alcohol, chloroform and acetone, difficult to dissolve in water. Yields of obtained compounds was satisfactory (76-84%). The purity of the obtained compounds was determined by TLC. The structure of the obtained compounds was proved by elemental analysis, IR methods and 1H NMR spectroscopy.NMR 1H spectra were recorded at BrukerWM spectrometer (200 MHz); solvent DMSO-d6; chemical shifts were in ppm, internal standard (TMS (tetramethylsilane)) was used. The prognosis of biological activity for obtained compounds were carried out using the program PASS (Prediction of Activity Spectra for Substances) in order toplan the further pharmacological screening. The program PASS predicts more than 500 kinds of biological activity using the chemical structural formula and helps to narrow the limits of experimental screening to identify compounds-leaders. This program is used just to assess the affinity of new compounds with known drugs, that is, to characterize their «drug likeness». The calculation was conducted with the help of Internet service that offers the software package of processing of listed structures and calculation of properties. Results and discussion: Synthesis of new potential biological active substances 2-R1-N (5-R)-1,3,4-thiadiazol-2-ilbenzolsulfonamides has been carried out. Finished products have been obtained by the interaction of 2-amino-5-(R)-1,3,4-thiadiazoles with corresponding substituted benzolsulfochlorides in the presence of anhydrous pyridine. Target products have been obtained with satisfactory yields. All semi-products have two-proton signal of aminogroup in the area from 2.5 to 2.82 ppm in NMR1Н spectra. Signals of protons substituents in the second position of the heterocycle (methyl, propyl, i-propyl, butyl, sec-butyl) on corresponding areas of spectra is present in NMR1Н spectra of the all initial compounds aswell. In contrast to the spectrums of initial compounds signals of amino groups at the spectra of the finished compounds are absent. All spectra of the target products have the secondary amino group signal at 6.81 and 6.71 ppm areas. The purity of the obtained compounds determined by TLC. Prediction of biological activity derived substances was conducted using a computer program PASS. Conclusion: The group of 2-R1-N-(5-R)-1,3,4-thiadiazol-2-ylbenzolsulfonamides has been synthesized by acylation of the corresponding 2-amino-5 -(R)-1,3,4-thiadiazoles. The structures of the synthesized compounds have been proved by elemental analysis, IR and 1H NMR spectroscopy data. All substances for which the PASS program prognosis was carried out can show themselves as potential antidiabetic and antimycobacterial drugs.